Examining Financial Sustainability of Fee-Free Secondary Education in Tanzania - Shemwelekwa, Rogers Jacob; Kahangwa, George Kahangwa (Papers in Education and Development, 2022)
This study was undertaken to examine financial sustainability in the provision of secondary education through a fee-free education policy in Tanzania. A concurrent embedded mixed research design was adopted. Data were collected from 421 respondents through stratified random, simple random and purposive sampling techniques using questionnaires, interviews, focus group discussion, and documentary review. Quantitative data was analysed using descriptive and inferential statistics analysis whereas qualitative data was analysed through thematic data analysis. Among others, the findings indicate that financial sustainability of feefree secondary education relies on the national financial and strategic planning. As one survival strategy, this study recommends schools to establish various income generating projects. Keywords: fee-free education, secondary education, sustainable education, Tanzania